Piloting an Intervention to Improve Outcomes in Young Adults Living With Type 1 Diabetes: The Experience of the D1 Now Support Worker - Lowry, Michelle; Morrissey, Eimear C.; Dinneen, Sean F. (Frontiers in Clinical Diabetes and Healthcare, 2021)
Introduction D1 Now is a novel intervention which aims to support self-management and clinic engagement and improve outcomes in young adults (18-25 years) living with type 1 diabetes in Ireland. It has been developed using a systematic, theoretical, user-centred approach. The specific role of the Support Worker, one of three components of the D1 Now intervention, was developed to provide continuity and build relationships between young adults and their diabetes team. Methods A Support Worker - an Occupational Therapist, who had a background in youth mental health - was hired as part of the D1 Now pilot randomised controlled trial and was based in one intervention site to join the existing diabetes team. Discussion The Support Worker aimed to provide an accessible and consistent point of contact for young adults, facilitated conversations about distress, and encouraged graded goal setting and collaborative problem solving. The role afforded her with a unique window into the lived experiences of young adults with type 1 diabetes where she observed the ongoing negotiation of life and living alongside diabetes care and management. The prevalence of diabetes distress was high in the study cohort with particular challenges associated with ‘all or nothing’ thinking patterns as well as disordered eating behaviours. The Support Worker also played an advocacy role in supporting the diabetes team’s awareness of young adults’ needs and explored current barriers to care. Preliminary findings from the D1 Now pilot have identified that the role of the Support Worker was viewed positively from the perspective of young adults with type 1 diabetes.